Low serum mannose-binding lectin level increases the risk of death due to pneumococcal infection - Eisen, Damon P; Dean, Melinda M; Boermeester, Marja A; Fidler, Katy J; Gordon, Anthony C; Kronborg, Gitte; Kun, Jürgen F J; Lau, Yu Lung; Payeras, Antonis; Valdimarsson, Helgi; Brett, Stephen J; Ip, W K Eddie; et al. (Clinical infectious diseases, 2008)
Previous studies have shown associations between low mannose-binding lectin (MBL) level or variant MBL2 genotype and sepsis susceptibility. However, MBL deficiency has not been rigorously defined, and associations with sepsis outcomes have not been subjected to multivariable analysis. We reanalyzed MBL results in a large cohort with use of individual data from 4 studies involving a total of 1642 healthy control subjects and systematically defined a reliable deficiency cutoff. Subsequently, data were reassessed to extend previous MBL and sepsis associations, with adjustment for known outcome predictors. We reanalyzed individual data from 675 patients from 5 adult studies and 1 pediatric study of MBL and severe bacterial infection. XA/O and O/O MBL2 genotypes had the lowest median MBL concentrations. Receiver operating characteristic analysis revealed that an MBL cutoff value of 0.5 microg/mL was a reliable predictor of low-producing MBL2 genotypes (sensitivity, 82%; specificity, 82%; negative predictive value, 98%). MBL deficiency was associated with increased likelihood of death among patients with severe bacterial infection (odds ratio, 2.11; 95% confidence interval, 1.30-3.43). In intensive care unit-based studies, there was a trend toward increased risk of death among MBL-deficient patients (odds ratio, 1.58; 95% confidence interval, 0.90-2.77) after adjustment for Acute Physiology and Chronic Health Enquiry II score. The risk of death was increased among MBL-deficient patients with Streptococcus pneumoniae infection (odds ratio, 5.62; 95% confidence interval, 1.27-24.92) after adjustment for bacteremia, comorbidities, and age. We defined a serum level for MBL deficiency that can be used with confidence in future studies of MBL disease associations. The risk of death was increased among MBL-deficient patients with severe pneumococcal infection, highlighting the pathogenic significance of this innate immune defence protein.